Introducing food additives - Guinness, Martin; Cove, Michael; Video Education Australasia (Bendigo, Vic.: Video Education Australasia, 1997)
Examines the topic of food additives: the range used, how additives can improve nutritional value, and food regulations and labelling applied to food additives.
Presented by Renee Brack.
Keywords: Food additives